Translation strategy in reading comprehension among good and poor learners of non - arabic speakers - Mustapha, Nik Farhan; Mustapha, Nik Hanan; Chik, Abdul Rahman (University of Malaya, 2016)
Translation is regarded as one of the strategies widely used by second or foreign language learners despite the controversy regarding the use of the mother tongue in language learning, and reading process. Good and poor language learners have both been reported to employ this strategy, though the extent of their reading comprehension varies. Based on a qualitative approach, this study investigated Arabic learners’ use of translation strategy in reading an academic Arabic text. Seven university students participated in this study. Data were collected by means of think aloud and observation. The results reveal that Arabic learners, regardless of their proficiency level, very often resort to their mother tongue in comprehending the Arabic text at different linguistic levels: words, structures and sentences. Good learners demonstrated an efficient way of using this strategy for comprehension, while poor learners failed to do so, thus, affecting their reading comprehension.